2021
DOI: 10.1080/19490976.2021.1960134
|View full text |Cite
|
Sign up to set email alerts
|

Imaging the in vivo growth patterns of bacteria in human gut Microbiota

Abstract: How to study the unculturable bacteria in the laboratory is one of the major challenges in human gut microbiota research. The resulting lack of microbiology knowledge of this “dark matter” greatly hinders further understanding of our gut microbiota. Here, to characterize the in vivo growth and division of human gut bacteria, we report the integrative use of STAMP (sequential tagging with D-amino acid–based metabolic probes) and fluorescence in situ hybridization (F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…Especially, the metabolic method was recently exploited to label live bacterial monosaccharides, such as N-acetylgalactosamine (GalNAc), 24 3-deoxy-D-mannooctulosonic acid (KDO), 25 N-acetylglucosamine (GlcNAc), 26 and peptidoglycan. 27 Our results revealed that the chemoenzymatic probe is compatible with both live and fixed bacteria. In the future, combining metabolic and chemoenzymatic methods to label bacteria will assist in the development of bacteria imaging.…”
Section: ■ Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Especially, the metabolic method was recently exploited to label live bacterial monosaccharides, such as N-acetylgalactosamine (GalNAc), 24 3-deoxy-D-mannooctulosonic acid (KDO), 25 N-acetylglucosamine (GlcNAc), 26 and peptidoglycan. 27 Our results revealed that the chemoenzymatic probe is compatible with both live and fixed bacteria. In the future, combining metabolic and chemoenzymatic methods to label bacteria will assist in the development of bacteria imaging.…”
Section: ■ Discussionmentioning
confidence: 54%
“…Furthermore, antibody labeling, lectin labeling, antibiotic labeling, and metabolic labeling were the main methods for labeling the oligosaccharide enveloped on bacteria, whereas our results enriched this territory. Especially, the metabolic method was recently exploited to label live bacterial monosaccharides, such as N-acetylgalactosamine (GalNAc), 3-deoxy- d -mannooctulosonic acid (KDO), N-acetylglucosamine (GlcNAc), and peptidoglycan . Our results revealed that the chemoenzymatic probe is compatible with both live and fixed bacteria.…”
Section: Discussionmentioning
confidence: 81%
“…Wang et al. [ 42,43 ] invented sequential tagging with d ‐amino acid‐based metabolic probes (STAMP) to assess the microbiota activity in fecal microbiota transplantations. Gut microbiota from FDAA‐labeled donor mice were transplanted into recipient mice, which were then treated with another FDAA probe of a different color.…”
Section: Novel Metabolic Labeling Imagingmentioning
confidence: 99%
“…[39,40] Lin et al [41] combined FDAA probes with FISH to develop two FDAA probes that could image intestinal flora in two colors, TAMRA-amino-d-alanine (TADA) and Cy5-amino-d-alanine (Cy5ADA), thereby visualizing different division patterns and growth rates of bacteria in vivo. Wang et al [42,43] invented sequential tagging with d-amino acid-based metabolic probes (STAMP) to assess the microbiota activity in fecal microbiota transplantations. Gut microbiota from FDAAlabeled donor mice were transplanted into recipient mice, which were then treated with another FDAA probe of a different color.…”
Section: Novel Metabolic Labeling Imagingmentioning
confidence: 99%
“…For example, The GF diet should be as low in fiber as possible and nutrients such as vitamins, minerals, and amino acids should be supplemented additionally compared to the SPF diet ( 24 , 25 ). Our laboratory has been studying the diets of GF animals and has formulated diets that meet the growth and reproductive needs of GF mice ( 26 ). The GF diet has a higher nutritional content than the SPF diet, both as previously reported and in the formulas we have created.…”
Section: Introductionmentioning
confidence: 99%